Effect of Perioperative β-Blockers on Pulmonary Complications among Patients with Chronic Obstructive Pulmonary Disease Undergoing Lung Resection Surgery. (1st September 2015) - Kamath, A.; Stover, D. E.; Hemdan, A.; Belinskaya, I.; Steingart, R. M.; Taur, Y.; Feinstein, M. B.
Abstract : The aim of this study is to determine if COPD patients undergoing lung resection with perioperative β -blocker use are more likely to suffer postoperative COPD exacerbations than those that did not receive perioperative β -blockers. Methods. A historical cohort study of COPD patients, undergoing lung resection surgery at Memorial Sloan-Kettering Cancer Center between 2002 and 2006. Primary outcomes were the rate of postoperative COPD exacerbations, defined as any initiation or increase of glucocorticoids for documented bronchospasm. Results. 520 patients with COPD were identified who underwent lung resection. Of these, 205 (39%) received perioperative β -blockers and 315 (61%) did not. COPD was mild among 361 patients (69% of all patients), moderate in 117 patients (23%), and severe in 42 patients (8%). COPD exacerbations occurred among 11 (5.4%) patients who received perioperative β -blockers and among 20 (6.3%) patients who did not. Secondary outcomes, which included respiratory failure, 30-day mortality, and the presence or absence of any cardiovascular complication, ICU transfer, cardiovascular complication, or readmission within 30 days, did not differ in prevalence between the two groups. Conclusions. This study implies that perioperative β -blockers use among COPD patients undergoing lung resection surgery does not impact the rate of exacerbations.